Why is Rentak Kudo Dance Important to be Preserved for the Kerinci Community? - Rahmayanti, Ririn; Novela, Putri (Contemporary Society and Politics Journal, 2023)
The purpose of this research is to describe and explain the values inherent in the art of Rentak Kudo, which is a tradition passed down through generations among the Hamparan Rawang community, particularly in the village of Tanjung. Rentak Kudo dance is commonly known as using “ntek awo”. Everyone who hears the song becomes enthusiastic, and their feet start to move like a horse. This type of research uses qualitative methods. Interviews, observations, and documentation are used as data collection techniques. The results of this study show that Rentak Kudo is a tradition that continues to thrive in the Rawang and Kerinci communities, despite the influence of modern culture. The values inherent in Rentak Kudo include cultural tradition values (customs), cultural preservation values, artistic values, harmony and togetherness values, recreational values, and economic values.